Sondagens arqueológicas no monte da Ola, Vila Fria, Viana do Castelo (Norte de Portugal) - Dinis, António; Bettencourt, Ana (PORTVGALIA: Revista de Arqueologia do Departamento de Ciências e Técnicas do Património da Faculdade de Letras da Universidade do Porto, 2018)
This article draws upon the recent archaeological excavations at the site of Monte da Ola (Viana do Castelo). This site was disturbed by urban development from 1920’s. Then earthworks uncovered important archaeological finds, which are kept in the Museu Municipal de Viana do Castelo. The excavations, integrated in the project The Entre-Douro-e-Minho landscape since middle of III to the end of II millenium BC, corroborated the existence of a cemetery dating to the Bronze Age.